SYSTEM DESIGN OF ADMINISTRATIVE LETTER SIGN IN PT. INHUTANI I - Trubus Sudarmanto; Irfan, SKom, MM Irfan, SKom, MM (Jurnal Sistem Informasi, 1999)
Pengagendaan process more efficient and effective letter because the process is only done once at the Directorate General, recording more orderly, the distribution of data throughout the unit more quickly if it is possible to develop kepaparless. Search data faster, supports the work atmosphere of mutual support (Synergistic).